Perancangan Media Promosi Desain Aplikasi Mobile Tentang Tepung Mocaf Pengganti Tepung Terigu Pada UMKM Arum Ayu Healthy Local Food - Hasian, Irene; Segara, Adi; Safira, Ishma (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2022)
Micro, Small and Medium Enterprises (MSMEs) are a category of small-scale businesses that are believed to be able to contribute to the Indonesian economy. One of the most preferred MSME businesses, even by young people, is the culinary business. One of them is MSME Arum Ayu Healthy Local Food as a supplier of gluten-free cassava flour (mocaf flour) in Tangerang Banten, in addition to selling raw materials for mocaf flour, it also provides a variety of Indonesian food made from tuber flour (gluten-free). Mocaf flour is a modification of cassava flour with a fermentation technique so that the resulting product has characteristics similar to wheat flour, soft white and no cassava taste so that the viscosity is better. Not many people are familiar with mocaf flour and its benefits and this is an obstacle for Arum Ayu Healthy Local Food SMEs in distributing their products. Therefore, Arum Ayu Healthy Local Food SMEs in carrying out promotions using online media mobile applications, where mobile applications are made with a visual approach in order to provide education about mocaf flour and build partnerships to expand business networks through resellers or drop shippers.